2020
DOI: 10.1186/s12903-020-01300-6
|View full text |Cite
|
Sign up to set email alerts
|

An objective system for appraising clear aligner treatment difficulty: clear aligner treatment complexity assessment tool (CAT–CAT)

Abstract: Background Recent years have witnessed a remarkable evolution of clear aligner technology and clear aligners are becoming more and more versatile in treating orthodontic patients. The aim of this study was to develop an objective evaluation system for assessing clear aligner treatment difficulty. Methods A total of 120 eligible patients (100 patients for developing and testing the evaluation system and 20 patients for validating this system) were recruited in this retrospective cross-sectional study. Based o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…With the development of orthodontic materials and advances in orthodontic techniques, clear aligner appeals to orthodontic patients for its comfort and ease of oral hygiene care. (22,23) A recent treatment-di culty evaluation system on clear aligner revealed that clear aligner had its distinct biochemical system and different types of di cult tooth movements as compared to xed appliances, (24) suggesting that clear aligner may require more additional anchorage than xed appliances. A recent nite-element study revealed that an anterior inter-radicular miniscrew between central incisors was effective for incisor intrusion and palatal torquing during anterior retraction.…”
Section: Complications Associated With Tadsmentioning
confidence: 99%
“…With the development of orthodontic materials and advances in orthodontic techniques, clear aligner appeals to orthodontic patients for its comfort and ease of oral hygiene care. (22,23) A recent treatment-di culty evaluation system on clear aligner revealed that clear aligner had its distinct biochemical system and different types of di cult tooth movements as compared to xed appliances, (24) suggesting that clear aligner may require more additional anchorage than xed appliances. A recent nite-element study revealed that an anterior inter-radicular miniscrew between central incisors was effective for incisor intrusion and palatal torquing during anterior retraction.…”
Section: Complications Associated With Tadsmentioning
confidence: 99%
“…The alternative using ceramic or composite resin aesthetic brackets was well received, but certainly the most welcome option is removable and transparent aligners [ 26 , 29 , 30 , 31 ]. Clear aligners are now widely used to treat not only simple cases, but also moderately complex or severely complex cases, even in the form of hybrid therapies [ 46 , 47 , 48 , 49 ]. In fact, clear aligner systems have substantially evolved both from a mechanical standpoint, with respect to the strategies that can be implemented to move teeth, and from a design and manufacturing perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for clear aligner (CA) therapy has increased dramatically thanks to its advantages of aesthetics, therapeutic comfort, and engagement of new biomaterial [ 1 ]. It has been reported that the number of clinical cases for the treatment of malocclusion via CA is continuously growing and approaching to the number of cases treated by conventional technique, fixed appliances (FA) [ 2 , 3 ]. However, it is suggested that CA therapy is mainly performed for non-extraction cases with minimal root movement [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%